INFLUENCE OF CLONAL ROOTSTOCKS ON GROWTH AND PRODUCTIVITY OF NURSERY APPLE TREES FOR ORGANIC PRODUCTION - Hulko Б. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The study of growth, development and productivity of standard nursery trees of new apple scab-resistant varieties depending on clonal rootstocks was carried out in the nursery in the test field of the Department of Horticulture and Vegetables Пrowing named after prof. I. P. Hulko of Lviv NEU. The experiment included new introduced apple varieties, which were the best, according to the preliminary study in the collection orchard in Lviv region, immune to the apple scab pathogen: Solnyshko, Williams Pride and Luna on clonal rootstocks: 62-396, 62-223, MM.102 and Don 70-456. The Florina variety, being immune to scab apple, was selected as standard. Spacing of plants in the nursery was 0.9×0.2 m (55 thousand plants/ha). Over the years, the following results have been obtained. The largest diameter of nursery trees was showed by Williams Pride variety (18.4–22.2 mm), slightly less were Luna trees (16.6–22.0 mm). Florina trees had an average diameter of 13.1–17.1 mm. This indicator was slightly smaller than the Solnyshko trees with the diameter that was the smallest (13.1–16.1 mm). The heights of nursery trees were as follows: the highest trees were of Florina variety (177.6–194 cm), Solnyshko trees were little lower (169.9–181.3 cm), and Williams Pride and Luna trees were the lowest – 164.0–173.5 cm and 162.5–175.9 cm, respectively. In general, the researchers can conclude that the nursery trees of Florina and Solnyshko varieties have a biological tendency to form tall but thin trees on all studied rootstocks. The Williams Pride and Luna varieties develop trees of smaller height, but with larger diameter. In terms of height and diameter, all studied combinations of rootstocks met the requirements of the standard for one-year trees on dwarf rootstocks. As for the Williams Pride variety, the majority of trees developed a crown at the age of one year and had a lot of fruit spurs and buds. Regarding the influence of rootstocks on the development of tees of different varieties, the authors of the research noted a positive effect of rootstock 62–223 in which the height and diameter were the largest. A higher productivity of standard trees on different dwarf rootstocks was provided by Williams Pride and Luna varieties on all studied rootstocks (more than 40 thousand trees/ha), Florina variety (38.6–41.0 thousand trees/ha) provided lower productivity. The Solnyshko variety was the least productive (37.7–40.0 thousand trees/ha) that was confirmed by the results of statistical processing of the obtained results. In all studied variants, rootstocks 62–223 and MM.102 provided a higher productivity than the control variant 62-396. The number of standard trees was 37.7–46.0 thousand/ha and fluctuated slightly depending on the rootstocks. The rootstock 62–223 provided greater productivity for the Florina, Williams Pride and Luna varieties – 41.0; 46.0 and 44.6 thousand pieces/ha, respectively, and for the Solnyshko variety, the best productivity was provided by MM.102 – 40.0 thousand pieces/ha. The productivity of Solnyshko nursery trees was lower than the control and was the lowest in our experiment: 37.7–40.0 thousand trees/ha. Higher profits from the nursery trees cultivation were got from Florina, Williams Pride and Luna varieties, i.e. on the rootstock 62–223: 996.0; 1166.3 and 1118.6 thousand UAH/ha, respectively. In the Solnyshko variety, on the rootstock MM.102, it was 962.0 thousand UAH/ha. The cost of growing one apple nursery tree of the studied varieties also depended on rootstocks and ranged from 9.6 UAH/piece (Williams Pride on 62–223) to 11.6 UAH/piece. (Solnyshko on 62–396). Growing of apple nursery trees is profitable on all studied rootstocks, but higher profitability of production for characteristic of the Florina, Williams Pride and Luna varieties provided on the rootstocks 62–223 – 226.9; 262.9 and 252.9 %, whilst for the Solnyshko variety trees it was lower than the control on all rootstocks.